Genetic diversity in oil palm (Elaeis guineensis and Elaeis oleifera) germplasm as revealed by microsatellite (SSR) markers - SUNILKUMAR, K; MURUGESAN, P; MATHUR, R K; RAJESH, M K (The Indian Journal of Agricultural Sciences, 2020)
Genetic variability and relationship of 29 germplasm accessions of two species, viz. Elaeis guineensis Jacq (25 accessions) and Elaeis oleifera (4 accessions) along with two Palode teneras were evaluated at ICAR-Indian Institute of Oil Palm Research, Regional Station, Palode, India during 2014-2016 with an objective to assess the germplasm diversity.Nine oil palms specific SSR primer pairs were used to assess the genetic diversity. All the nine primer pairs produced reproducible unambiguous markers. The total number of alleles per primer pair varied from six (sMo00129, sMo00128, mEgCIR3890, sMo00130, mEgCIR0268, mEgCIR0905, sMo00020, sMo00154,) to seventeen (mEgCIR3399). It produced a total of 107 alleles from the selected two oil palm species and all the makers were polymorphic. Cluster analysis, based on UPGMA was performed in order to realize the extent of similarity/ dissimilarity among the germplasm accessions. The dendrogram showed two major clusters at 0.09 similarity coefficient one with E. oleifera and other with E. guineensis. Among E. oleifera, Chithara (Oleifera palms identified in the commercial plantation owned by OPIL, Kerala) accessions were grouped separately indicating confirmation of distinctness. Among E. guineensis accessions, G1(Nigerian dwarf tenera) and G55 (Tanzanian dura) showed maximum diversity. Evaluation data obtained in this study on the ‘extent of genetic distance’ among accessions can be explored carefully for planning hybridization programme so as to accelerate palm oil yield by maximizing the hybrid vigour. The significant genetic diversity observed among the germplasm accessions indicated the scope of introgression into the current breeding programme.